BUDAYA HUKUM DALAM PELAKSANAAN UNDANG-UNDANG PERLINDUNGAN KONSUMEN DI ERA TRANSAKSI ONLINE - Rumbiak, Joan Rossy; Maritza, Allya Lavenia; Mansur, Habil Ma’ruf; Sari, Elsi Kartika (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: Buying and selling transactions are very important economic activities in human life. The development of information technology has changed the way we transact, one of which is the rise of online buying and selling transactions. The main problem that is the focus of this study is what factors influence the level of legal awareness of sellers and consumers in online transactions and what obstacles are faced in implementing the Consumer Protection Law in the era of online transactions. This study uses the Normative Legal Research and Empirical Legal Research methods because they focus on legal principles and focus on social realities regarding people's legal awareness in the era of online transactions. The results of this study indicate that the factors that influence the level of legal awareness of a seller and consumer are in the education factor, both formal and non-formal education, because it can determine the extent to which a seller/consumer can have an understanding of the importance of selling with the standards referred to in the UUPK, other factors are experience, profit motivation, and age. The obstacles faced in online buying and selling transactions are the broad and dynamic scope of transactions, Unclear Seller Identity, Misleading Product Quality and Information, Low Consumer Legal Awareness, and Imperfect Regulations in dealing with the phenomenon of online transactions.Keywords: Online Buying and Selling Transactions, Legal Culture, Legal Awareness